Exposure to ultraviolet radiation late in development increases the toxicity of oil to mahi‐mahi (Coryphaena hippurus) embryos. (19th December 2016) - Sweet, Lauren E.; Magnuson, Jason; Garner, T. Ross; Alloy, Matthew M.; Stieglitz, John D.; Benetti, Daniel; Grosell, Martin; Roberts, Aaron P.
Abstract: The Deepwater Horizon oil spill in 2010 overlapped with the spawning of many pelagic fish species in the Gulf of Mexico, including mahi‐mahi ( Coryphaena hippurus ). Polycyclic aromatic hydrocarbons (PAHs) released during the spill have been shown to cause photo‐induced toxicity under ultraviolet (UV) radiation. In the present study, mahi‐mahi embryos were exposed to high‐energy water accommodated fractions of source and naturally weathered oils for up to 48 h. The timing of co‐exposure with UV radiation varied between an early development exposure for 8 h or a late development exposure for 8 h. The UV co‐exposure had a photo‐induced toxic effect on hatching success for all oil types and exposure scenarios. A more sensitive developmental window to photo‐induced toxicity was observed when UV exposure occurred late in development. Source Oil B was over 6‐fold more toxic, and Massachusetts source oil was 1.6‐fold more toxic when the embryos were co‐exposed to UV light late in development. Furthermore, weathered oil from the surface co‐exposure with UV late in development resulted in bradycardia in the mahi‐mahi. The present study provides evidence that the developmental window when UV co‐exposure occurs has a significant effect on the degree of photo‐induced toxicity of oil and that UV co‐exposure may exacerbate long‐term cardiac effects in developing fish. Environ Toxicol Chem 2017;36:1592–1598. © 2016 SETAC